Morpho-arrangement study of the anthropogenic landform for potential exposure of tsunami hazard identification in parangtritis, yogyakarta - Mardiatno, D.; Malawani, M.N.; Iswari, M.Y.; Listyaningrum, N.; Hafizah, K.N. (Institute of Physics, 2022)
This research was conducted in the tsunami prone area of Parangtritis, Yogyakarta. The purpose of this study is to classify and analyse the distribution of anthropogenic landforms, as preliminary information to identify the potential exposure to tsunami. The method used in this research is descriptive-comparative, i.e. by comparing the variations of anthropogenic landforms typology within the present management zones (core, restricted, supporting zone). For each zone, the type of human intervention were identified with regard to the following classification: industrogenic, urbanogenic, traffic, agrogenic, water management, tourism, and sports. The anthropogenic landforms are then classified into excavation, planation, and accumulation types. The results of the study were presented in the form of tables and maps of anthropogenic landforms in each management zone. Assessment of the level of exposure to tsunami hazard is carried out qualitatively for each anthropogenic landform in the different management zones. This research revealed that type of intervention in each management zone are varied. The supporting zone and restricted zone have the most complex interventions, i.e. industrogenic, urbanogenic, traffic, water management, tourism, and sports. The excavation, planation, and accumulation forms are very diverse, depend on the people activities in each management zone. A particular human activity in the study area has a certain level of exposure to tsunami hazard. It is necessary to consider for reducing the specific risk to tsunami. © 2022 Institute of Physics Publishing. All rights reserved.